2019
DOI: 10.1016/j.pnpbp.2018.07.021
|View full text |Cite
|
Sign up to set email alerts
|

The need to improve detection and treatment of physical pain of homeless people with schizophrenia and bipolar disorders. Results from the French Housing First Study

Abstract: Physical pain was highly reported in homeless patients with severe mental illness with insufficient care. Physical pain should be systematically explored and treated in this population. Bipolar disorders, antidepressant consumption and female gender may be targeted in priority. Age and psychotic symptomatology were found to influence self-reported pain in a marginal way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
(43 reference statements)
1
8
0
Order By: Relevance
“…Higher levels of pain were significantly related to psychotropic medication use. Similar studies support this finding with users of psychotropic drugs reporting poor pain control [ 42 , 43 ]. Helstrom and colleagues (2018) found that chronic pain was identified in 14% of 250 older adults who were recently prescribed a psychotropic medication, who also reported pain interference with daily activities [ 44 ].…”
Section: Discussionsupporting
confidence: 71%
“…Higher levels of pain were significantly related to psychotropic medication use. Similar studies support this finding with users of psychotropic drugs reporting poor pain control [ 42 , 43 ]. Helstrom and colleagues (2018) found that chronic pain was identified in 14% of 250 older adults who were recently prescribed a psychotropic medication, who also reported pain interference with daily activities [ 44 ].…”
Section: Discussionsupporting
confidence: 71%
“…The search was done by experts on schizophrenia (two psychologists, two dentists, two psychiatrists, and two nurses). They screened 46 papers, selected nine (8,12,14,(21)(22)(23)(24)(25)(26), and engaged in discussion until a consensus was reached at the end of the third meeting. This process involved 3 consensus meeting.…”
Section: Interview Guidementioning
confidence: 99%
“…In this context, further studies are needed to improve the management of their oral health and OHRQoL, potentially with the use of specific prevention and education programs. The challenge is to identify people who are not willing to care for themselves and identify the importance that they place on their quality of life including treatments, 12 dental pain management, 13 or OHRQoL 14 to expand the understanding of the factors that limit or facilitate the healthcare pathway. In other words, determining the significance that PWS place in oral health and OHRQoL warrants investigation.…”
Section: Introductionmentioning
confidence: 99%
“…A recent multicenter study evaluated the prevalence of physical pain in a sample of 655 schizophrenia and bipolar disorder patients who were homeless [28]. While less than 3% were receiving analgesic treatment, more than half of the sample reported moderate to severe physical pain.…”
Section: The Association Between Pain and Psychotropic Medications Inmentioning
confidence: 99%
“…No association was found between antipsychotics, mood stabilizers, anxiolytics, hypnotics, or medication adherence and self-reported pain. However, to some extent, the severity of psychotic symptoms (e.g., the relative absence of antipsychotic medication) increased the reporting of physical pain [28]. This suggests that antipsychotics may, indeed, reduce pain or else that the pain reported in the context of severe psychotic symptoms is a form of delusional sensation.…”
Section: The Association Between Pain and Psychotropic Medications Inmentioning
confidence: 99%